ASSESSMENT OF PROFITABILITY OF SHEA BUTTER (VITELLARIA PARADOXA) PROCESSING IN NORTH CENTRAL NIGERIA (FUDMA JOURNAL OF SCIENCES, 2023)
The study examined the profitability and constraints to Shea butter in Makwa local government area of Niger state. A multistage sampling technique was used to collect information from the 139 respondents. The data collected were analysed using descriptive statistics, budgeting analysis and five point likert scale. The results show that respondents mean age was 54years. Most of the respondents 87(67.58%) were married, and 2(1.02%) had tertiary education. The profitability analysis shows that the variable costs cost (VC) of (N2899715) accounted for more than 98% of the total cost. (TC) cost for the respondents was N2953359 with an estimated fixed cost (FC) of N53644.72. The total revenue accrued to the enterprise was estimated at N8321582 per month with a net return of about N 5368222.28. The enterprise has an estimated Benefit cost ratio of 2.82 and a rate of returns on investment of about 1.82 indicating that the enterprise is profitable and worthwhile. Poor access to credit facilities and poor extension services were the most serious challenges of the enterprise with an aggregate mean score of 412 and 411 respectively. Also, inadequate inputs (341) was ranked third most important constraints as most processors still rely on traditional equipment for storing their products. The study recommended that respondents should form associations and cooperative societies to enable them take advantage of group actions for better access to credit facilities. Also, the government, research institutes and Non-Governmental organisations should step up action on extension activities directed at the Shea butter enterprise.
Keywords: : Profitability, Constraints Processing, Marketing and Shea Butter